2022
DOI: 10.1158/1078-0432.ccr-21-4011
|View full text |Cite
|
Sign up to set email alerts
|

VCAM-1–targeted MRI Improves Detection of the Tumor-brain Interface

Abstract: Purpose: Despite optimal local therapy, tumor cell invasion into normal brain parenchyma frequently results in recurrence in patients with solid tumors. The aim of this study was to determine whether microvascular inflammation can be targeted to better delineate the tumor-brain interface through vascular cell adhesion molecule-1 (VCAM-1)-targeted MRI. Experimental Design: Intracerebral xenograft rat models of MDA231Br-GFP (br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…Further, histological analysis showed marked endothelial VCAM-1 expression at the margins of the tumours, and single MPIO bound to VCAM-1 positive blood vessels. These data are in accord with previous studies in the micrometastatic stages of the 4T1-GFP model 47,49 and other macrometastasis models 52 showing that antibody-conjugated MPIO are capable of sensitive and specific imaging of VCAM-1 positive blood vessels. However, neither of the two animals imaged with IgG-MPIO showed any MRI-detectable hypointensities or macrophage uptake by immunohistochemistry, in line with our previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Further, histological analysis showed marked endothelial VCAM-1 expression at the margins of the tumours, and single MPIO bound to VCAM-1 positive blood vessels. These data are in accord with previous studies in the micrometastatic stages of the 4T1-GFP model 47,49 and other macrometastasis models 52 showing that antibody-conjugated MPIO are capable of sensitive and specific imaging of VCAM-1 positive blood vessels. However, neither of the two animals imaged with IgG-MPIO showed any MRI-detectable hypointensities or macrophage uptake by immunohistochemistry, in line with our previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…To this end, a CINC-1 induced model of BBB breakdown was used. As non-specific accumulation of MPIO had not previously been observed in models of brain macrometastasis when targeted with antibodies rather than peptides 52 , both peptide- and antibody-targeted MPIO were again evaluated. BBB breakdown was confirmed in all animals using gadolinium-enhanced imaging (Supplementary Figure 9A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 A study has found that inflammation for brain metastases from breast cancer can be detected from magnetic resonance imaging (MRI). 7 Additionally, breast, lung, and melanoma primaries are more likely to yield multiple brain metastases, while tumors of the gastrointestinal tract are more likely to seed the posterior fossa. 8 Such patterns are readily visible on MRI examinations and have been previously noted in population studies.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Preclinical studies using rodent models have demonstrated early detection of BrMs by employing molecular MRI with contrast agents that highlight tumor vascular factors ALCAM21 and VCAM-1. [38][39][40] Routine pre-operative and post-operative imaging should also be considered: a study by Yokoi, et al, showed that CT and MRI detected brain metastases in 6.8% and 7.1% of 155 and 177 patients, respectively, during the perioperative period for patients with non-squamous cell lung cancer. [41] Preclinical rodent studies have also indicated that brain metastases can be diagnosed even at micrometastatic stages by screening for urine metabolites; however, these were not specific for lung cancer.…”
Section: Introductionmentioning
confidence: 99%